Feasibility of Using Jackfruit Seed Powder as a Substitute of Skimmed Milk Powder for Making Traditional Yoghurt (Journal of the Bangladesh Agricultural University, 2020)
This research work was carried out to determine the optimum quantity of jackfruit seeds powder to substitute skimmed milk powder (SMP) for yoghurt preparation. Total six yoghurt samples were prepared where one is control (A) and rest five samples were prepared by mixing different ratios of jackfruit seeds powder and SMP. 0%, 0.75%, 1.5%, 2.25% and 3% of jackfruit seeds powder were mixed with 3%, 2.25%, 1.5%. 0.75% and 0% SMP and designated as B, C, D, E and F respectively. Physical, chemical and microbiological and cost analysis of prepared samples were done. Yoghurt sample (D) showed highest score in total physical test but individual score for body and consistency of sample F is maximum. Solubility % of jackfruit seeds powder were found 10.96. Highest acidity level was found in control yoghurt and highest pH in sample F. Maximum fat content (g/kg) was found in sample F, but utmost protein content was found in sample (B). Total solids, ash and carbohydrate content of sample F were significantly higher (p